Amino Acid Transporter Inventory of the Selaginella Genome - Wipf, Daniel; Loqué, Dominique; Lalonde, Sylvie; Frommer, Wolf B. (Frontiers in Plant Science, 2012)
Amino acids play fundamental roles in a multitude of functions including protein synthesis, hormone metabolism, nerve transmission, cell growth, production of metabolic energy, nucleobase synthesis, nitrogen metabolism and urea biosynthesis. Selaginella as a member of the lycophytes is part of an ancient lineage of vascular plants that had arisen ~400 million years ago. In angiosperms, which have attracted most of the attention for nutrient distribution so far, we have been able to identify many of the key transporters for nitrogen. Their role is not always fully clear, thus an analysis of Selaginella as a representative of an ancient vascular plant may help shedding light on the evolution and function of these diverse transporters. Here we analyze the genes for transporters involved in cellular uptake of amino acids present in the Selaginella genome.